Hukuman Dalam Hadis Tentang Perintah Shalat: (Tinjauan Sosiologi dan Psikologi Pendidikan Islam) - Mahfud Mahfud (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
The problem of moral decline and behavioral changes of students both in social and psychological settings is the reason for this research. Children's lack of attention to religious norms often occurs in the global society. At the same time, technological advances have not only brought positive impacts but also negative impacts where parents often forget the moral messages that must be carried out in religious life. Law enforcement for the sake of child discipline has the same tendency between personal matters and religious interests. As a result, children often become victims of violence in the family and forget the responsibility of forming children with Islamic personalities. Part of the problem is the lack of understanding of the content of the hadith regarding the obligation of parents to educate their children to pray. How is the model of punishment contained in the hadith about the command to pray. How to review the sociology and psychology of Islamic education about the punishment model contained in the hadith about the command to pray.